Patient-Computer Dialogue: A Review, - Slack, W.V. (Yearbook of Medical Informatics, 2000)
Since the first study of communication between patient and computer was performed at the University of Wisconsin in 1965, programs for patient-computer dialogue have been developed, implemented, and studied in numerous settings in the United States and abroad, and the results have been encouraging. This review presents a brief history of patient-computer dialogue together with suggested guidelines for programs in the future.
Keywords: cybermedicine; patient-computer dialogue; computers; interviews; medical history taking; user-computer interface; self-care; patient power; patient satisfaction